Hypoxia Activates Notch4 via ERK/JNK/P38 MAPK Signaling Pathways to Promote Lung Adenocarcinoma Progression and Metastasis - Li, Xiaochen; Cao, Xiaopei; Zhao, Hanqiu; Guo, Mingzhou; Fang, Xiaoyu; Li, Ke; Qin, Lu; He, Yuanzhou; Liu, Xiansheng (Frontiers in cell and developmental biology, 2021)
Hypoxia contributes to the progression and metastasis of lung adenocarcinoma (LUAD). However, the specific underlying molecular mechanisms have not been fully elucidated. Here we report that Notch4 is upregulated in lung tissue from lung cancer patients. Functionally, Hypoxia activates the expressions of Delta-like 4 and Notch4, resulting in the excessive proliferation and migration of LUAD cells as well as apoptotic resistance. Notch4 silencing reduced ERK, JNK, and P38 activation. Meanwhile, Notch4 overexpression enhanced ERK, JNK, and P38 activation in LUAD cells. Furthermore, Notch4 exerted pro-proliferation, anti-apoptosis and pro-migration effects on LUAD cells that were partly reversed by the inhibitors of ERK, JNK, and p38. The binding interaction between Notch4 and ERK/JNK/P38 were confirmed by the co-immunoprecipitation assay. In vivo study revealed that Notch4 played a key role in the growth and metastasis of LUAD using two xenograft models. This study demonstrates that hypoxia activates Notch4-ERK/JNK/P38 MAPK signaling pathways to promote LUAD cell progression and metastasis.